A global environmental right - Turner, Stephen J. (Stephen James) (Abingdon, Oxon : Routledge, 2014)
'The development of an international substantive environmental right on a global level has long been a contested issue. To a limited extent environmental rights have developed in a fragmented way through different legal regimes. This book examines the potential for the development of a global environmental right that would create legal duties for all types of decision-makers and provide the bedrock for a new system of international environmental governance.
Taking a problem solving approach, the book seeks to demonstrate how straightforward and logical changes to the existing global legal architecture would address some of the fundamental root causes of environmental degradation. It puts forward a draft global environmental right that would integrate duties for both state and non-state actors within reformed systems of environmental governance and a rational framework for business and industry to adhere to in order that those systems could be made operational. It also examines the failures of the existing international climate change regime and explains how the draft global environmental right could remedy existing deficits.
This innovative and interdisciplinary book will be of great interest to policy-makers, students and researchers in international environmental law, climate change, environmental politics and global environmental governance as well as those studying the WTO, international trade law, human rights law, constitutional law and corporate law.'--pub. desc.
The state of degradation of the planet's environment, the impact upon human rights and the current status of the development of environmental rights -- Global environmental governance, the global legal architecture and the root causes of environmental degradation -- A global environmental right : draft with commentary -- The application of the draft global environmental right the climate change.
Includes bibliographical references (pages 166-180) and index.
Keywords: Environmental law, International